ANALISIS PERAN PUSAT KESEJAHTERAAN SOSIAL DALAM MENANGGULANGI PERMASALAHAN KEMISKINAN DI KELURAHAN WATU-WATU KOTA KENDARI - Darpin Darpin; Syamsul Alam; Yusfira Nurul Alyzah (Universitas Halu Oleo, 2022)
The purpose of this study is to find out the role of social welfare centers and efforts in tackling poverty in Watu-Watu Village, West Kendari District, Kendari City, Southeast Sulawesi. The research method in this study is qualitative descriptive that describes the data obtained on the ground. The data obtained from interviews with informants are Village Leader of Watu-Watu, Chairman of Watu-Watu Village Health Center, Officer or staff of Watu-Watu Puskesos, and the community. The data obtained is then analyzed and drawn conclusions. The results of this study, based on the results of analysis and discussion that has been outlined, that the role of social welfare centers (Puskesos) in tackling the problem of poverty using social services directly, namely Providing social services, social services for advocacy, ease of accessibility and data and information providers. While poverty reduction efforts use three strategies, namely the provision of basic needs, the development of social assistance and social security systems, and the development of poor business culture that can be said to be good, But there are indicators that have not run in accordance with community expectations, namely regarding the indication of the role, Puskesos has played a role but there are still those that have not been fulfilled, namely in social services for advocacy so as to make the community uncomfortable in receiving the assistance provided.